Rhizogenesis in Shrub rose cultivated in vitro - Yevhen Mazur; Alla Konopelko; Iryna Denysko; Larysa Koldar (Trakya University Journal of Natural Sciences)
The study of the reproduction characteristics of roses of the garden class Shrub, the defini-tion of the dependence of the hormonal determination of explant rhizogenesis on the con-centrations of phytohormones that are part of the nutrient medium, are relevant and has both scientific and practical interest. This study presents the results of studies of hormonal de-termination of rhizogenesis in explants of cultivars of roses of the garden class Shrub: Gärt-nerfreude, Lavender Dream, Pomponella, Red Cascade, Sommerabend cultivated in vitro on nutrient medium containing growth regulators. It has been established that of the nutrient medium modified by the addition of 0.2-1.0 mg/l α-naphthylacetic acid (α-NAA), the most effective was the medium with the content of α-NAA 0.5 mg/l, the content of macro- and microelements half of the Murashige and Skoog prescriptions, and a decrease in the sucrose content to 2.0%. On this medium, the frequency of rhizogenesis averaged 61.2% for the studied cultivars. Hormonal determination of rhizogenesis and efficiency of root formation in vitro in the Shrub rose regenerants depended on the genotype of the plant: cv. Lavender Dream (66.0%) and cv. Sommerabend (67.0%) had the highest rhizogenesis ability. The use of the universal growth regulator Humifield in combination with 0.5 mg/l α-NAA contribut-ed to an increase in the rooting rate of the studied rose cultivars up to 70.0-86.0%.